Dependence of nonlinear coupling among turbulence, geodesic acoustic modes and tearing modes on magnetic island width in the HL-2A edge plasmas. (1st December 2022) - Xu, J.Q.; Li, J.C.; Peng, X.D.; Qu, Y.R.; Lin, Z.; Jiang, M.; Huang, Z.H.; Wu, N.; Wang, W.C.; Hao, G.Z.; Chen, W.; Qu, H.P.; et al.
Abstract: Statistical spectral features of the dependence of geodesic acoustic modes (GAMs) and their nonlinear couplings with ambient turbulence on the magnetic island (MI) width ( W ) in the edge region of HL-2A tokamak plasmas are analyzed. Experimental observations have indicated that the modulation influence as well as the strength of nonlinear interactions between GAMs and turbulence generally shows a gradual decay while the couplings between MIs and the latter are increased simultaneously as the MI becomes larger. The MIs mainly reduce the couplings between GAMs and potential fluctuations, whereas the changes in the nonlinear interactions between density fluctuations and MIs are more evident. Moreover, it is found that there exists a nonmonotonic relationship between the turbulence correlation length and island width, in which it exhibits a minimum around W ∼ 3.7 cm, suggesting that the MI around such a scale would have a significant suppression effect on turbulent transport. These findings promote the understanding of the nonlinear interactions between MIs and turbulence in the edge of fusion plasmas.